Braddock–Carey syndrome: A 21q22 contiguous gene syndrome encompassing RUNX1. Issue 10 (23rd August 2016) - Braddock, Stephen R.; South, Sarah T.; Schiffman, Joshua D.; Longhurst, Maria; Rowe, Leslie R.; Carey, John C.
Abstract : In 1994, Braddock and Carey first reported two unrelated girls with a new multiple malformation syndrome. The primary features included Pierre Robin sequence, persistent neonatal‐onset thrombocytopenia, agenesis of the corpus callosum, a distinctive facies, enamel hypoplasia, and severe developmental delay. Since that time, there have been multiple other reported patients with a similar phenotype. In addition, several reports of thrombocytopenia and developmental delay have been documented in association with deletions in the Down syndrome critical region at 21q22. The similarity of the reported cases with deletions involving 21q22 with the clinical presentation of the two patients with Braddock–Carey syndrome resulted in a reinvestigation of the genetic etiology of these two patients 20 years after the original study. This investigation provides evidence that the etiology of this and other "Fanconi‐like" disorders represent a newly recognized contiguous gene deletion syndrome involving 21q22 and specifically, the RUNX1 gene. © 2016 Wiley Periodicals, Inc.